SIMPLE AND FAST PROCEDURE TO INCORPORATE DOXORUBICINE IN SMALL UNILAMELLAR LIPOSOMES: EFFECTS ON LIPOSOME SIZE AND ZETA POTENTIAL - SOCACIU, Mihai Adrian; DIACONEASA, Zorita; SOCACIU, Carmen (Studia Universitatis Babeș-Bolyai Chemia, 2019)
This study aimed to find alternative, cheap and fast procedures to incorporate Doxorubicin in small unilamellar nanoliposomes made of Dipalmitoyl Phosphatidyl Choline and Cholesterol. It was compared the entrapment efficiency of doxorubicin in home-made liposomes (1) and in ImmunoSOME liposomes (2), a commercial, expensive formulation. It was obtained an entrapment efficiency of 27.6 % vs 12.1% for formulatios (1) vs (2). The liposomes’ size and zeta-potential of formulation (1) ranged from 116 and 120 nm, being smaller than in formulation (2). The zeta potential was negative for both formulations and showed a better stability and monodispersibility also for formulation (1). This fast procedure is convenient and assure efficient doxorubicin entrapment in the monodisperse nanoliposomes. Such simple formulations, easier to be obtained, can offer also good quality/ price ratios and can be produced at larger scale, with higher incorporation efficiency for experimental in vivo studies which aims the targeted delivery of Doxorubicin to cancer tumors in animals.